Pembelajaran Aljabar yang Kontekstual: Studi Eksperimen Model CTL dan Media Kartu Elemen Aljabar - Faelasofi, Rahma; Sari, Intan Puspita; Nihayati (Universitas Muhammadiyah Kotabumi, 2025)
This research focuses on assessing the enhancement of students' performance in mathematics through the application of the Contextual Teaching and Learning (CTL) approach, supported by algebra element cards specifically in the area of algebraic expressions. The study employs a quantitative method with a comparative framework. The target population includes seventh- grade students from UPT SMPN 2 Gading Rejo. A sample was drawn from two classes selected by a cluster random sampling method, where VII A served as the experimental group utilizing the CTL approach along with algebra element card media, while VII B acted as the control group engaging with a traditional teaching model that also incorporated algebra element cards. The subsequent data analysis utilized the Mann-Whitney Test due to the data not satisfying the normality assumption. The results of the data analysis show that , thus it can be concluded that the CTL learning model assisted by algebra element card media has a significant effect on improving the mathematics learning outcomes of the 7th-grade students of UPT SMPN 2 Gading Rejo